2021
DOI: 10.1039/d0qm00623h
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional AIE-ESIPT dual mechanism tetraphenylethene-based Schiff base for inkless rewritable paper and a colorimetric/fluorescent dual-channel Zn2+ sensor

Abstract: Organic fluorescent materials have attracted extensive interests due to their wide applications. However, many organic fluorescent materials are single functional and suffer from complicated synthesis and purification, which significantly limits...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 57 publications
0
31
0
1
Order By: Relevance
“…Considering that Schiff-base derivatives are good metal-binding ligands, [46][47][48] we attempted to employ L NPs and L-NDI LHS NPs to fabricate a dual-color mode detector for metal ions. A preliminary uorescence quenching experiment showed that both L NPs and L-NDI NPs exhibit good responsiveness towards Cu 2+ (Fig.…”
Section: Fluorescent Probe For Cu 2+ Sensingmentioning
confidence: 99%
“…Considering that Schiff-base derivatives are good metal-binding ligands, [46][47][48] we attempted to employ L NPs and L-NDI LHS NPs to fabricate a dual-color mode detector for metal ions. A preliminary uorescence quenching experiment showed that both L NPs and L-NDI NPs exhibit good responsiveness towards Cu 2+ (Fig.…”
Section: Fluorescent Probe For Cu 2+ Sensingmentioning
confidence: 99%
“…Blue emission was achieved from the AIE fluorophore tetraphenylethylene (TPE) linked by zinc cation into coordination supramolecular polymers. Recently, Zhonghai Ni [ 125 ] developed an ESIPT-based AIEgen Schiff-base compound containing a tetraphenylethene skeleton preventing the ACQ effect. Both the absorption and fluorescence spectra are water- and Zn(II)-responsive.…”
Section: Zn Aiegens For Oleds and Other Optical Technologiesmentioning
confidence: 99%
“…TPESB was employed for dual-channel sensing of Zn 2+ with high selectivity and sensitivity exhibiting a low limit of detection of 38.9 nM. Thus due to its low cytotoxicity, the probe is applied for sensing of Zn 2+ in live cells [ 49 ]. In this work, He et al designed a “turn-on” fluorescent probe with TPE as AIE active fluorophore combined with the peptide chain.…”
Section: Aggregation Induced Emission (Aie) Active Molecules For Sensing Applicationmentioning
confidence: 99%